Chronic hepatitis D—What is changing?. Issue 4 (19th February 2022) - Yardeni, David; Heller, Theo; Koh, Christopher
Abstract: Hepatitis D virus (HDV) infection is a chronic viral disease of the liver that is still largely considered to be incurable due to lack of effective treatment options. Without treatment, the risk for the development of advanced liver disease, cirrhosis and hepatocellular carcinoma is significantly high. Currently, new therapeutic options are emerging out of ongoing phase 3 clinical trials, promising a new hope of cure for this devastating liver infection. Recently, bulevirtide, a first in its class HDV entry inhibitor, has received conditional authorization of use from the European Medicines Agency (EMA) and was also submitted for approval in the United States. Other novel therapeutic options in clincal trials include interferon lambda, the prenylation inhibitor lonafarnib and nucleic acidic polymers (NAPs). This review describes all recent advances and ongoing changes to the field of HDV therpaeutics.